Motivation and Parental Supervision Improve Indonesian Language Learning Outcomes - Muhammad Agus Halim; Ni Wayan Rati (Journal for Lesson and Learning Studies, 2023)
The learning process carried out by students is still low. This is because students are less motivated in learning. The purpose of this study is to analyze parental motivation and supervision on Indonesian language learning outcomes. This type of research is quantitative research. The subjects in this study were 30 grade IV students. The methods used in collecting data are interviews, questionnaires, observation, and documentation. The instrument used in collecting data is a questionnaire. The technique used to analyze the data is descriptive qualitative-quantitative. The results of the t test show that there is a partial positive influence of parental supervision variables on learning outcome variables. Based on the results of the large test of influence together on learning motivation and parental supervision on learning outcomes. The results of the multiple regression test showed that there was a significant influence on learning motivation and parental control variables on the Indonesian language learning outcomes. It was concluded that learning motivation and parental supervision can improve learning outcomes in Indonesian for fourth grade elementary school students. The implication of this research is that increasing motivation and parental supervision of children has an impact on increasing children's learning outcomes, especially in Indonesian language lessons.